Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) terhadap Pemahaman Materi Tata Krama dalam Pendidikan Agama Islam dan Budi Pekerti - Shale Afif; Susi Hidayat; Afif Nurseha; Ajat Saputra (Jurnal Pendidikan Educandum, 2025)
The research problems in this study are how the influence of students' initial understanding of etiquette material, how the influence of the Numbered Head Together (NHT) learning model on student understanding, and how the differences in understanding between experimental and control groups in learning etiquette. The research method uses true experimental with pretest-posttest group design, involving an experimental group implementing the Numbered Head Together (NHT) learning model and a control group. The results show: first, there is a significant influence of students' initial understanding of etiquette material (significance 0.000 less than 0.05) with an average pretest score of 6,29; second, the Numbered Head Together (NHT) learning model has a significant effect on increasing student understanding, shown by an average posttest score of 17.59; third, there are significant differences between the experimental group (average 16,94) and control group (average 11,82), proving the effectiveness of the Numbered Head Together (NHT) learning model in improving students' understanding of etiquette compared.